Development of an enhanced hybrid bi-catalytic electrode containing bimetallic composite catalyst and immobilized enzyme for complete glucose electrooxidation - Franco, Jefferson Honorio [UNESP]; Bonaldo, João Victor; da Silva, Rodrigo Garcia; Minteer, Shelley D.; De Andrade, Adalgisa R. [UNESP] (Elsevier, 2023)
We describe an enzymatic fuel cell (EFC) that can electrooxidize glucose completely. The EFC contains the hybrid Ni@Pt-CNT/OxOx bioanode, composed of a bimetallic composite catalyst (Ni@Pt-CNT) and the enzyme oxalate oxidase (OxOx), which can cleave carbon-carbon bonds. Ni@Pt-CNT/OxOx displayed 3-fold higher catalytic activity in the presence than in the absence of glucose (1.3 and 0.4 mA cm−2, respectively), indicating that Ni@Pt-CNT and OxOx acted synergistically. Electrochemical impedance spectroscopy showed that Ni@Pt-CNT/OxOx had higher charge transfer resistance and double layer capacitance than Ni@Pt-CNT. Long-term bulk electrolysis (18 h) revealed that the EFC operating with Ni@Pt-CNT/OxOx presented better current density and stability than the electrochemical cell operating with Ni@Pt-CNT, so deep glucose electrooxidation generated energy. The glucose oxidation products detected by HPLC-UV/RID confirmed that glucose was fully electrooxidized, and that 24 electrons were harvested from it. The hybrid Ni@Pt-CNT/OxOx bioanode developed herein could be used in cascade reactions, to provide an EFC with promising application in self-powered electronic devices.
Keywords: Enzymatic biofuel cell; Glucose; Hybrid system; Metallic catalyst; Oxalate oxidase